Gamma-radiation-induced phosphorylation of p53 on serine 15 is dose-dependent in MOLT-4 leukaemia cells - Tichý, A; Záskodová, D; Zoelzer, F; Vávrová, J; Sinkorová, Z; Pejchal, J; Osterreicher, J; Rezácová, M (Folia biologica, 2009)
Molecular indicators of the absorbed dose of ionizing radiation are powerful tools in biodosimetry. The studies reported here were undertaken with the motivation to find such a marker among the mo lecules involved in ataxia-telangiectasia mutated kinase- dependent signalling induced by ionizing radiation (ATM-kinase, checkpoint kinase-2, protein p53, and oncoprotein Mdm2). In our previous work on T-lymphocyte leukaemia MOLT-4 cells we described the mentioned molecules of ATM-dependent pathway and none of them showed a pronounced dosedependent response. Here we employed Western blotting and ELISA assay to investigate the response of post-translationally modified p53 (particularly phosphorylated on serine 15) after gamma-irradiation. We have found the amount of phosphorylated p53 to be homogenously increased after irradiation by the doses of 0.5 to 7.5 Gy. The dose-dependent response was pronounced especially after the doses up to 3.0 Gy. The presented data indicate that p53 phosphorylated on serine 15 might be used as a potential biodosimetric marker.
Keywords: leukemie; proliferace buněk; fosforylace; Leukemia; Humans; Serine; Gamma Rays; Phosphorylation; lidé; Tumor Suppressor Protein p53; záření gama; Cell Proliferation; Cell Line, Tumor; serin; nádorový supresorový protein p53; nádorové buněčné linie